2020
DOI: 10.3390/pr8121651
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Porous Carbon for Wastewater Treatment

Abstract: Porous materials constitute an attractive research field due to their high specific surfaces; high chemical stabilities; abundant pores; special electrical, optical, thermal, and mechanical properties; and their often higher reactivities. These materials are currently generating a great deal of enthusiasm, and they have been used in large and diverse applications, such as those relating to sensors and biosensors, catalysis and biocatalysis, separation and purification techniques, acoustic and electrical insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 228 publications
(301 reference statements)
1
20
0
Order By: Relevance
“…, materials with pores of different widths ( w ) that can be classified as micro-, meso-, and macropores ( w < 2 nm, 2 < w < 50 nm, and 50 nm < w , respectively), have attracted the interest of the chemistry and engineering scientific community due to their versatility. Carbon precursors are abundant in nature and, depending on their origin and processing, the obtained HPCs can exhibit an interesting combination of characteristics that make them suitable for a wide range of applications like gas adsorption and separation, , wastewater treatment, drug delivery and bioimaging, catalysis, , energy storage in batteries and supercapacitors, hydrogen storage, among others. , For instance, it has been shown that a hierarchical porous carbon (HPC) with ordered mesopores connected through narrow micropores can be used as a molecular sieve for the separation of linear and branched alkanes . Moreover, HPCs with ordered or disordered structures had also been tested as electrodes for supercapacitors or batteries, showing that the well-connected hierarchical micro–mesopore structure provides short diffusion paths for ions and electrons, resulting in high-rate capabilities of the assembled energy storage devices. , …”
Section: Introductionmentioning
confidence: 99%
“…, materials with pores of different widths ( w ) that can be classified as micro-, meso-, and macropores ( w < 2 nm, 2 < w < 50 nm, and 50 nm < w , respectively), have attracted the interest of the chemistry and engineering scientific community due to their versatility. Carbon precursors are abundant in nature and, depending on their origin and processing, the obtained HPCs can exhibit an interesting combination of characteristics that make them suitable for a wide range of applications like gas adsorption and separation, , wastewater treatment, drug delivery and bioimaging, catalysis, , energy storage in batteries and supercapacitors, hydrogen storage, among others. , For instance, it has been shown that a hierarchical porous carbon (HPC) with ordered mesopores connected through narrow micropores can be used as a molecular sieve for the separation of linear and branched alkanes . Moreover, HPCs with ordered or disordered structures had also been tested as electrodes for supercapacitors or batteries, showing that the well-connected hierarchical micro–mesopore structure provides short diffusion paths for ions and electrons, resulting in high-rate capabilities of the assembled energy storage devices. , …”
Section: Introductionmentioning
confidence: 99%
“…MF is used for chemical wastewater treatment, which is aimed at removing nonsettling particles, heavy metals, phosphorus compounds [27], and toxic organic substances [9]. Common chemical processes used for greywater treatment include ion exchange filtration [15].…”
Section: Membrane Filter (Mf) Process With Activated Carbon (Ac) and Coconut Coir (Cc)mentioning
confidence: 99%
“…The adsorption of pollutants through pore-filling mechanism depends on the total pore volume of the porous network of the carbon nanomaterial and also is dependent on the size of pollutants [209]. The p-p stacking interactions are attributed to the sorption of aromatic compounds on the surface of carbon nanomaterials containing aromatic rings such as graphenes [210].…”
Section: Mechanisms Of Adsorption Of Pollutantsmentioning
confidence: 99%
“…The removal of pollutants may also possible through adsorption and degradation processes at the surface of carbon nanomaterials. In some studies, the main mechanism of removal of pollutants is photocatalytic degradation as observed in the presence of g-C 3 N 4 or CQDs, whereas the adsorption mechanism is considered as accessorial process [157,209,220]. The photocatalytic decomposition of organic pollutants takes place through a mechanism which is based on photoexcited electrons of the photocatalysts such as g-C 3 N 4 or fullurene/CQDs and their composites which are able to generate holes (h + ) and exited electrons (e -) in the conduction band.…”
Section: Mechanisms Of Adsorption Of Pollutantsmentioning
confidence: 99%